Brown Adipose Tissue Activation by Cold Treatment Ameliorates Polycystic Ovary Syndrome in Rat - Ye, Rongcai; Yan, Chunlong; Zhou, Huiqiao; Huang, Yuanyuan; Dong, Meng; Zhang, Hanlin; Jiang, Xiaoxiao; Yuan, Shouli; Chen, Li; Jiang, Rui; Cheng, Ziyu; Zheng, Kexin; et al. (Frontiers in Endocrinology, 2021)
Polycystic ovary syndrome (PCOS) is a common endocrine disease accompanied by energetic metabolic imbalance. Because the etiology of PCOS is complex and remains unclear, there is no effective and specific treatment for PCOS. It is often accompanied by various metabolic disorders such as obesity, insulin resistances, and others. Activated brown adipose tissue (BAT) consumes excess energy via thermogenesis, which has positive effects on energy metabolism. Our previous research and that of others indicates that BAT activity is decreased in PCOS patients, and exogenous BAT transplantation can improve PCOS rodents. Notably however, it is difficult to apply this therapeutic strategy in clinical practice. Therapeutic strategies of enhancing endogenous BAT activity and restoring whole-body endocrine homeostasis may be more meaningful for PCOS treatment. In the current study, the dehydroepiandrosterone-induced PCOS rat was exposed to low temperature for 20 days. The results show that cold treatment could reverse acyclicity of the estrous cycle and reduce circulating testosterone and luteinizing hormone in PCOS rats by activating endogenous BAT. It also significantly reduced the expression of steroidogenic enzymes as well as inflammatory factors in the ovaries of PCOS rats. Histological investigations revealed that cold treatment could significantly reduce ovary cystic follicles and increase corpus luteum, indicating that ovulation was recovered to a normal level. Concordant with these results, cold treatment also improved fertility in PCOS rats. Collectively, these findings suggest that cold treatment could be a novel therapeutic strategy for PCOS.